PROYEKSI BIAYA PERSEDIAAN BAHAN BAKU KANTONG SEMEN DENGAN METODE ECONOMIC ORDER QUANTITY - Rizky Nofatriani; Siska Aprianti; Sulaiman Sulaiman; Rita Martini (EKSISTANSI, 2021)
This study aims to analyze management of the cost control of inventory of bag raw materials and frequency orders with EOQ methods, ReOrder Point and Safety Stock at PT Semen Baturaja (Persero), Tbk. For handling costs of supplies there is inefficiencies of costs raw material bags PCC 50 Kg. Inefficiencies borne by the company is quite material, seen from the many types of raw materials. ReOrder Point in 2018 for booking planning and accurate purchase of raw materials is 78,493 and for 2019 of 75,493 units, the Safety Stock of 2018 and 2019 was obtained for 156,986 and 150,658. The simulation results in the next 5 (five) years for 12 raw materials and the helper material is projected in 4 plant there will be an additional stock cost of Rp 1.065.269.485, while the projection of spare parts for 1,000 materials will be an additional supply fee of Rp 17,754,491,417.